Strategi Komunikasi Posyandu Mawar 22 Dalam Program Pekan Imunisasi Nasional Di Sukatani Depok - Nanda Annisa, Rani Dwi; Irwanto, Irwanto (Mu'ashir: Jurnal Dakwah dan Komunikasi Islam, 2023)
Polio is a disease that attacks the nerves and the worst impact can cause permanent paralysis. Polio was found in children as young as 4 years old in Karawang. This has caused the West Java region to be declared an Extraordinary Event (KLB). Because of this, the West Java Health Office held a National Immunization Week to prevent transmission to other children. In the implementation at Posyandu Mawar 22 children who are immunized have not reached the desired target. The purpose of this study was to determine the communication strategy of Posyandu cadres in socializing the National Immunization Week program at Posyandu Mawar 22 Sukatani. The research method used is descriptive qualitative method. Based on the results of research and discussion conducted by researchers, the communication strategy used by Posyandu cadres is that first the cadres get training or direction regarding what the PIN program is and also determine the target audience for the socialization of the PIN program, compiling messages for socialization in the form of what the PIN program is, how important the PIN program is to do, the socialization method is carried out directly or by intermediary whatsapp media, and for the media used is an online poster.